Small Water-Plane Area Corvette: Algorithm and Example of Designing - Dubrovsky, Victor (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Corvettes and patrol ships with various roles are more or less important parts of various fleets. Usually the corvettes are high-speed (21-35 knots) ships of restricted displacement (from 600 up to 3000 t). This means some essential restrictions of operability by waves. Therefore, the development of the corvette’s seaworthiness is an important need of the future fleet. Ships with a small water-plane area, SWA ships, differ from all displacement ones by having the highest achievable seakeeping and by minimal losses of speed in waves. A concept of SWA corvette is designed by a special algorithm and proposed for the world market.